“Nietzsche in Law’s Cathedral: Beyond Reason and Postmodernism” - John Linarelli (Catholic University Law Review, 2004)
Selected for publication in Francis J. Mootz III & Peter Goodrich, Nietzsche and Law (Ashgate 2008)